The Development of a Model for Improving Revenue from Sales Tax on Services in Khyber Pakhtunkhwa, Pakistan - Khan, Naveed (2024)
Pakistan exhibits one of the lowest tax-to-GDP ratios globally. This causes poor public finances. Consequently, the country is unable to meet government operational expenses, infrastructure development, and socio-economic improvement. A detailed analysis shows a significant discrepancy between the tax revenue potential and actual tax collections among all the major sources of tax revenues. This is particularly true of the sales tax on services (STS). The existing literature underscores the inefficiency of the STS system in generating satisfactory revenues. Thus, to address deficiencies and enhance collection, the study examines the current STS framework and the factors affecting revenue collection. In pursuit of its objectives, the study adopts a qualitative research design, collecting data from three distinct groups, i.e., surveys of taxpayers, in-depth interviews of potential taxpayers, and discussion with the focus groups of officials dealing with STS matters. Data analysis was done using detailed descriptive analysis, thematic analysis and correlation. The study identified Tax Administration, System Effectiveness, and Revenue Mobilization as the major factors affecting tax revenue collections. In addition, the tax officials reported lack of resources and incentives for tax assessment and tax collection activities. The potential Taxpayers’ Group reported lack of Public Trust as one of the main factors influencing tax collection. Notably, the study is confined to the STS collections in Khyber Pakhtunkhwa Province. The study presents actionable steps for policymakers and tax collecting agencies to improve tax compliance and tax collection.